2021
DOI: 10.3389/fcell.2021.728057
|View full text |Cite
|
Sign up to set email alerts
|

Hlf Expression Marks Early Emergence of Hematopoietic Stem Cell Precursors With Adult Repopulating Potential and Fate

Abstract: In the aorta-gonad-mesonephros (AGM) region of mouse embryos, pre-hematopoietic stem cells (pre-HSCs) are generated from rare and specialized hemogenic endothelial cells (HECs) via endothelial-to-hematopoietic transition, followed by maturation into bona fide hematopoietic stem cells (HSCs). As HECs also generate a lot of hematopoietic progenitors not fated to HSCs, powerful tools that are pre-HSC/HSC-specific become urgently critical. Here, using the gene knockin strategy, we firstly developed an Hlf-tdTomato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
(82 reference statements)
1
5
0
Order By: Relevance
“…Moreover, Hlf expression does not mark EMPs within the yolk sac or endothelial cells of the yolk sac, AGM, or fetal liver ( Yokomizo et al, 2019 ). These observations were supported by the recent report by Tang et al (2021) . Compared with the unique Hlf expression in embryonic HSCs from E10.5 to E14.5, Hlf expression in non-hematopoietic cells remains elusive.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, Hlf expression does not mark EMPs within the yolk sac or endothelial cells of the yolk sac, AGM, or fetal liver ( Yokomizo et al, 2019 ). These observations were supported by the recent report by Tang et al (2021) . Compared with the unique Hlf expression in embryonic HSCs from E10.5 to E14.5, Hlf expression in non-hematopoietic cells remains elusive.…”
Section: Resultssupporting
confidence: 90%
“…Another recent study by Yokomizo et al 102 showed that FL HSCs do not contribute to FL hematopoiesis using lineage‐tracing mouse models. Hlf has recently been reported to be expressed in pre‐HSCs in the AGM region as well as in human HSCs 103–106 . They found that HlfCreERT2 specifically marked pre‐HSCs and not EMPs in the YS and that HlfCre ‐derived cells contributed to most hematopoietic progenitors in the FL, suggesting that Hlf + pre‐HSC populations contain greater percentages of HSC‐independent hematopoietic progenitors than HSCs.…”
Section: Hscs Do Not Contribute To Fl Hematopoiesis Including B‐proge...mentioning
confidence: 99%
“…Hlf has recently been reported to be expressed in pre-HSCs in the AGM region as well as in human HSCs. [103][104][105][106] They found that HlfCreERT2 specifically marked pre-HSCs and not EMPs in the YS and that HlfCre-derived cells contributed to most hematopoietic progenitors in the FL, suggesting that Hlf + pre-HSC populations contain greater percentages of HSC-independent hematopoietic progenitors than HSCs. Furthermore, Evi1 is highly expressed in the HSCs, and Evi1CreERT2 was able to specifically label HSCs in the FL.…”
Section: H Sc S Do Not Contribute To Fl Hematop Oie S Is In Clud Ing...mentioning
confidence: 99%
“…Bulk RNA-seq revealed that hPSC-derived day-10 hematopoietic progenitors and human embryonic DA CD144+ CD45+ HSCs 143 expressed comparable levels of HSC signature transcription factors, including HLF , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 HOPX , 160 NKX2.3 , 161 MEIS1 , 162 , 163 , 164 , 165 and HOXA genes ( HOXA5 , HOXA9 , and HOXA10 ) 62 , 65 , 74 ( Figures 6 B and S7 C). As a negative control, human DA CD144− CD45+ non-HSCs minimally expressed these HSC signature transcription factors ( Figures 6 B and S7 C).…”
Section: Resultsmentioning
confidence: 99%
“… 65 Hlf is required for HSC function 66 and constitutes an exquisitely specific HSC marker. 67 , 68 , 69 , 70 , 71 , 72 , 73 Likewise, HOXA5-10 are required for HSC function, 62 , 74 and forced expression of HOXA and other genes enhances the engraftment of hPSC-derived hematopoietic progenitors. 75 , 76 This underscores the importance of generating HLF + HOXA + hematopoietic progenitors from hPSCs and discovering the extracellular signals that ignite expression of these hallmark HSC markers.…”
Section: Introductionmentioning
confidence: 99%